Control-oriented thermal network models for predictive load management in Canadian houses with on-Site solar electricity generation: application to a research house. Issue 4 (4th July 2022) - Abtahi, Matin; Athienitis, Andreas; Delcroix, Benoit
Abstract : This paper presents a methodology for development of control-oriented thermal RC network models for optimized HVAC load management in typical electrically heated single-family two-storey detached houses in Québec, assuming that there are three zones and it is equipped with photovoltaics and battery storage. Using data from an unoccupied research house, two 3rd order RC networks are developed and calibrated. One model (3C6R network) assumes that each floor is a separate thermal zone, and the other model (3C7R network) assumes that the south-facing zone and the north-facing zone of the building are separate zones. Application of model predictive control with both developed models results in an average 12.1% reduction in the daily heating load, 19.8% reduction in the total daily electricity imported, 68.1% reduction in the peak demand, 67.0% reduction in the energy cost, and 13.4% increase in the self-consumption of on-site generated solar electricity compared to a traditional reactive controller.